Monolithic integration of glass-based optical devices via solution doping of erbium rare-earth material / Kow Siew Ting@Koh Siew Ting - Kow, Siew Ting (2009)
This thesis describes novel experimental methods in solution doping based on dipping (nonselective area) and dripping via a syringe/pipette (selective area doping). Silica soot layers deposited via Flame Hydrolysis Deposition were pre-sintered prior to solution doping. The doped pre-sintered soot was then consolidated to form dense silica layers. The variations in the number of pores, layer thickness, and dopant (erbium) concentration play major roles in the quality of the resulting glass layer. Optimisation and subsequent characterisation of the pre-sintered layers in terms of surface morphology and structure were carried out. It was found that samples pre-sintered at 850C were optimal, allowing solution doping to be performed. Saturation of the dipping period was achieved within 20 minutes following immersion of the sample into an erbium-trichloride in de-ionised water solution. In selective area doping, both single and multi-cycle dripping approaches were adopted. Erbium ion concentration increased as the number of droplets increases. Ring effects were also observed at high droplet counts.